Howship-Romberg Sign and Bowel Obstruction: A Case Report - Saeed, Rasha (Cureus, 2019)
Small bowel obstruction (SBO) is associated with high morbidity and mortality in acute care surgery practice, with hernias constituting a significant portion of the underlying etiology. Physical examination and maneuvers such as changing the extremity position of the patient can further improve clinician's diagnostic acumen to identify the cause of the disease. We present a case of SBO in an 83-year-old female whose physical exam was consistent with an underlying obturator hernia.